Commentary: Unexpected Benefits that Challenge the Orthodoxy of DBS Outcomes. (16th September 2016) - Ford, Paul
Abstract : The case of Ms. L. provides a wonderful opportunity to highlight the underlying value commitments that often deeply influence decisionmaking in medicine and more specifically in innovative neurosurgical procedures. In order to give a fair opinion on how Dr. Impf, as clinician and researcher, should act, a much richer and thicker understanding of the actual perspectives of the stakeholders would be necessary. Because this is not available, I highlight three important elements: the terms under which the deep brain stimulation (DBS) is implanted, the proper goals of a healthcare team, and the fallacy of a "natural" or immutable self. These elements are brought together in this case by a set of unexpected effects on the patient that were not intended and that are judged and categorized differently by various stakeholders within the case. In the end, I hope that there was full transparency and agreement about obligations, responsibilities, and outcomes prior to the implantation of the DBS between the physician and patient. Further, it is important to remember that just because a result is serendipitous does not mean that it should be discounted as a proper benefit. Finally, each person authors variations on their own self that are molded by environment and social networks. If Ms. L. continues to demonstrate an ability to author a desired self, the DBS is no more inappropriate a tool than many other artifacts that are used regularly by others to mold themselves.